Granulocytic myeloid‐derived suppressor cell population increases with the severity of alcoholic liver disease. Issue 3 (25th December 2018) - Gao, Miaomiao; Huang, Ang; Sun, Zijian; Sun, Ying; Chang, Binxia; Zhang, Ji‐yuan; Zou, Zheng‐sheng
Abstract: Alcoholic liver disease (ALD) is a progressive liver disease that can cause a series of complications, including cirrhosis, liver failure and hepatocellular carcinoma. Granulocytic myeloid‐derived suppressor cell (gMDSC) populations have been observed to expand in various liver diseases and to inhibit innate and adaptive immunity in patients with liver disease. However, the characteristics of gMDSCs in patients with ALD have not been studied. We studied 24 healthy controls (HCs) and 107 patients with ALD and found an accumulation of gMDSCs in the peripheral blood of patients with alcoholic liver cirrhosis (ALC). Furthermore, ALC patients with a poor prognosis displayed a significant increase in peripheral gMDSCs and showed an increased capacity for arginase I production compared to HCs. In contrast, plasma arginase I levels in ALC patients were negatively correlated with total bilirubin and international normalized ratio, two key parameters of liver damage. Importantly, gMDSCs accumulated in the livers of ALC patients, and the frequency of liver gMDSCs significantly correlated with that of peripheral gMDSCs. In addition, gMDSC enrichment in vitro significantly inhibited the function of natural killer (NK) cells, perhaps preventing the NK‐induced apoptosis of hepatic stellate cells. In summary, increased peripheral and intrahepatic gMDSC populations are present in patients with ALC and may contribute to enhancing the severity of liver cirrhosis.